Odpowiedzi

2010-02-09T20:20:18+01:00
Zad1.
A)-y+8x-z-2x= dla x=-2 , y=6,z=-3
-y+8x-z-2x=-6+8*(-2)-(-3)-2*(-2)=-6-16+3+4=-15

B)-8y-4z+x-y-2z+1= dla x=-0,5 , y=1 , z=2
-8y-4z+x-y-2z+1=-8*1-4*2+(-0,5)-1-2*2+1=-8-8-0,5-1-4+1=-20,5

C)9y-(7y+x)+6(x-7y)= dla x=-2, y=3
9y-(7y+x)+6(x-7y)=9y-7y-x+6x-42y=9*3-7*3-(-2)+6*(-2)-42*3=27-21+4-12-126=-128

2010-02-09T20:24:24+01:00
A)-y+8x-z-2x= dla x=-2 , y=6,z=-3
-6+8*(-2)-(-3)-2*(-2)=-6+16+6-4=26
B)-8y-4z+x-y-2z+1= dla x=-0,5 , y=1 , z=2
-8*1-4*2+(-0,5)-2*2+1=-8+8-0,5-4+1=3,5 sprawdz dokladnie
C)9y-(7y+x)+6(x-7y)= dla x=-2, y=3
9*3-[7*3+(-2)]+6(-2-7*3)=27-19+6*(-23)=8+(-138)=-146
D)(6a-8b-0,7)-(6,9+a-5b)+1,8= Dla a=-2,b=1/2 , c=-4
(6*-2-8*1/2-0,7)-[6,9+(-2)-5*1/2]+1,8=(-12-4-0,7)-(6,9-2-2,5)+1,8=-16,7-2+1,8=-16,9
E) 1/2abc-(4ab+2abc)+(-bc+5ab)= dla a=-2 , b=1/2 , c=-4
[1/2*(-2)*1/2*(-4)]-[4*(-2)*1/2+2*(-2)*1/2*(-4)]+[-1/2*(-4)+5*(-2)*1/2]=-2-4-8-3=-17